Challenges and critiques of the EU internal security strategy : rights, power and security - O'Neill, Maria (Senior lecturer); Swinton, Ken (Cambridge Scholars Publishing, 2017)
This collection of papers examines a variety of areas and issues related to, or raised by, the EU Internal Security Strategy. It covers such matters as critical infrastructure protection and environmental crime, from a range of disciplinary perspectives, including law, geography and politics. The EU Internal Security Strategy is becoming increasingly complex as it develops over time, as it has to operate against the background of growing diversity in law enforcement systems across EU member states. It is clear that the EU Internal Security Strategy is, and will continue to be for a long time, a.